Heterogeneity in the fiscal reaction function: An empirical analysis for EU member states - Bettina Bökemeier; Andreea Stoian; Bogdan Dumitrescu; Cosmin Cepoi (Bielefeld University, Faculty of Business Administration and Economics, 2020)
This paper studies heterogeneity in the fiscal reaction function for European Union members by resorting to the unconditional quantile regression estimation. Based on annual observations spanning from 2005 to 2018, the results point to significant asymmetries concerning the fiscal response measured in terms of the cyclically adjusted primary balance to different covariates. First, the primary deficit has a stronger reaction to debt across the lower quantile, which becomes weaker as the balance reaches a surplus. This indicates the prevalence of fiscal discipline to ensure the public finance sustainability. Moreover, the life-expectancy negatively affects the fiscal position and the response is the highest compared to other covariates, which can diminish the debt and business stabilizing response. Governments seem to run more pronounced pro-cyclical fiscal policy when the fiscal position is already deteriorated. These empirical evidences are questioning current as well as future policy design particularly against the background of the recent pandemic situation exerting supplementary social and financial burden on the countries. In addition, the level of economic development matters for the response pattern and the reaction is stronger and positive when countries face poorer fiscal positions. Also, an increase in the longterm interest rate amplifies the deterioration of fiscal balance especially when its condition is already bad. Finally, our estimations show that the fiscal position improves as an effect of educational attainment and of external position especially when the former reaches surplus.
urn:nbn:de:0070-pub-29515610
Keywords: C21; E62; H63; 330; Fiscal response function; Heterogeneity; Fiscal sustainability; Unconditional quantile regression